Pengaruh Belanja Modal, Infrastruktur dan Indeks Pembangunan Manusia terhadap Produk Domestik Regional Bruto di Provinsi Sumatera Selatan - Tino Handayani; Didik Susetyo; M. Syirod Saleh (Department of Development Economics, Universitas Sriwijaya, 2017)
The purpose of this research is to analyze the influence of capital expenditures, infrastructure of the long road, and the human development index (HDI) to GDP District/city in South Sumatera Province. The data used in this research is data from the year 2010-2015 results from publications of the Central Bureau of Statictic (BPS) and the Directorate General of Financial Equalization (DJPK). Location of research covering 15 District/City in South Sumatera Province. This research was conducted by means of panel data regression analysis using program of Eviews 8. The selection of late-model in this data regression analysis using program of Eviews 8. The selection of late-model in this study i.e the Fixed Effectmodel. The results showed that variable capital expenditures, infrastruture of the long road, and the human development index (HDI) are jointly significantly to GDP. The variable infrastucture of the long road and the shuman development index (HDI) a negative and siignificant effect against the GDP. The value of the coefficient of the determinaation (R-square) obtained the value of the variable 0.986993 which means capital expenditures, infrastucture of the long road, and the human development index is able to affect the GDP of 98.69 percent 1.31 percent and the rest is determined by other variables that are not listed in the model